Transparent app design reduces excessive usage time and increases willingness to pay compared to common behavioral design - A framed field experiment - Christina Timko; Maja Adena (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Smartphone app designers often use behavioral design to influence users, increase sales, and boost advertising revenue. Behavioral design relies on elements ranging from app appearance to black-box algorithms and personalization. It commonly exploits behavioral biases, such as the lack of self-control. Consumers are seldom aware of such design and usually have no control over it. Aiming to protect consumers, the recently enacted European Digital Services Act requires app design to be more transparent and adjustable. In a framed field experiment, we document that behavioral design increases app usage time, especially in the case of vulnerable users. An app version that adds transparency and offers protection features helps to overcome temptation. The higher willingness to pay for the transparent version shows that the positive effects of app transparency and increased consumer protection might not only materialize on the demand side but may also challenge current practices on the supply side.
Keywords: C93; O33; D83; L86; M38; D18; 330; smartphone app; filtering algorithm; transparency; consumer protection; field experiment